Surfacing Times and Dive Rates for Narwhals (Monodon monoceros) and Belugas (Delphinapterus leucas) - Heide-Jørgensen, M.P.; Hammeken, N.; Dietz, R.; Orr, J.; Richard, P.R. (ARCTIC, 2001)
Time spent at and near the sea surface was measured for 25 narwhals, Monodon monoceros, and 39 belugas or white whales, Delphinapterus leucas, in West Greenland and Canada from 1993 through 1999, using satellite-linked data recorders. Narwhals spent less time at the surface than belugas did, and the surfacing time of belugas also varied between localities. No clear differences in surfacing time were associated with the time of day, but belugas tended to make more dives during the night than during the day. Despite large variability in surfacing behaviour among individual whales, time spent at the surface by both species declined from August through November. The few data collected from narwhals from November to February indicate that surfacing times remained low during this period although more than 25% of each 6 h period was spent at the surface. Whales made between 2 and 20 dives per hour, and narwhals made significantly fewer dives than did belugas, for which number of dives varied with locality. The number of dives deeper than 8 m declined substantially during the autumn for belugas and narwhals that were moving offshore. When travelling, the whales apparently made fewer dives than at other times. De 1993 à fin 1999, on a mesuré le temps passé à la surface de la mer ou près de celle-ci par 25 narvals, Monodon monoceros, et 39 bélougas ou baleines blanches, Delphinapterus leucas, dans le Groenland occidental et au Canada, en recourant à des enregistreurs de données en liaison avec un satellite. Les narvals passaient moins de temps que les bélougas à la surface, et le temps passé par ces derniers en surface variait d'un endroit à un autre. Aucune différence marquée dans le temps de surface n'a été associé avec le moment de la journée, mais les bélougas avaient tendance à faire plus de plongées la nuit que le jour. Malgré une grande variabilité dans le comportement de surface parmi les baleines prises individuellement, le temps passé en surface par les deux espèces a diminué d'août à fin novembre. Les ...